Tax Impact on Household Income - Pavlova Mariyana (Economics and Business)
The household income is an important economic indicator because it determines the scale of the household sector consumption and its delay in future in terms of saving and investing. Many factors influence the magnitude of household income and one of these factors is taxation. Given the significance of tax payments not only for household income, and through them – for the national economy, the object of the current study is the household income and in particular the impact of the taxation framework on the formation of disposable income. The aim of the study is to examine the changes in the monetary income of households in the Republic of Bulgaria as a function of the implemented tax reforms in the period following the country’s accession to the EU.